Analisis Penyebab Ketidakcocokan Stock Opname Pada Divisi Spare Part Inventory Di Pt. Xyz - Hatta Makarim; Rusindiyanto Rusindiyanto (STIKes Ibnu Sina Ajibarang, 2024)
Warehouse is an important part of a company. Warehousing activities must have a good storage system to support the smooth production process and warehousing activities. PT. XYZ is a manufacturing company in the field of paper production that uses 100% recycled paper as its raw material. PT. XYZ has many warehouses needed for production. Stock taking is an activity of physically counting the inventory of goods in the warehouse or production to determine the real or actual quantity owned by the company. Stock taking is important to carry out control, so that the company can monitor and know the assets it owns. By carrying out comprehensive stock taking activities, real stock reports will be obtained which will be used as material for consideration for further development. One of the problems that often occurs in spare part warehouses is a mismatch in the final balance of spare part components between the stock card and the inventory system which occurs continuously. This problem can cause errors in stock taking reports which can result in losses for the company. This research uses the fishbone diagram method. This diagram is often called a cause and effect diagram. This fishbone diagram is used to analyze and look for factors causing problems that have a significant impact on differences in inventory. Human, environmental, material and method factors are factors that cause differences in existing inventory. Human factors such as drowsiness and lack of concentration can also be caused by environmental factors such as lack of air circulation, causing the temperature in the spare parts warehouse to increase. The lack of discipline of spare parts warehouse officers also greatly influences the results of stock taking activities carried out